Short message service reminder intervention doubles sexually transmitted infection/HIV re-testing rates among men who have sex with men. Issue 3 (4th February 2011) - Bourne, C; Knight, V; Guy, R; Wand, H; Lu, H; McNulty, A
Abstract : Objectives: To evaluate the impact of a short message service (SMS) reminder system on HIV/sexually transmitted infection (STI) re-testing rates among men who have sex with men (MSM). Methods: The SMS reminder programme started in late 2008 at a large Australian sexual health clinic. SMS reminders were recommended 3–6 monthly for MSM considered high-risk based on self-reported sexual behaviour. The evaluation compared HIV negative MSM who had a HIV/STI test between 1 January and 31 August 2010 and received a SMS reminder (SMS group) with those tested in the same time period (comparison group) and pre-SMS period (pre-SMS group, 1 January 2008 and 31 August 2008) who did not receive the SMS. HIV/STI re-testing rates were measured within 9 months for each group. Baseline characteristics were compared between study groups and multivariate logistic regression used to assess the association between SMS and re-testing and control for any imbalances in the study groups. Results: There were 714 HIV negative MSM in the SMS group, 1084 in the comparison group and 1753 in the pre-SMS group. In the SMS group, 64% were re-tested within 9 months compared to 30% in the comparison group (p<0.001) and 31% in the pre-SMS group (p<0.001). After adjusting for baseline differences, re-testing was 4.4 times more likely (95% CI 3.5 to 5.5) in the SMS group than the comparison group and 3.1 times more likely (95% CI 2.5 to 3.8) than the pre-SMS group. Conclusion: SMS reminders increased HIV/STI re-testing among HIV negative MSM. SMS offers a cheap, efficient system to increase HIV/STI re-testing in a busy clinical setting.